Investigation of Fe3O4 nanoparticles synthesized via co-precipitation coated with chitosan, PEG, and folate for targeted paclitaxel delivery in fibrosarcoma treatment - Adawiya Haider; Sharafaldin Al-Musawi; Rusul Al-Obaidy; Azhar Haleemd; Mohammed Al-Hindawi; Bakr Taha (Engineering and Technology Journal)
Magnetite (Fe3O4) nanoparticles (NPs) were synthesized using a straightforward co-precipitation method from Fe2+/Fe3+ salt solutions as starting materials. This method was optimized to control particle size and morphology, resulting in highly magnetic NPs with crystallite sizes ranging from 20 to 70 nm. The synthesis process involved magnetic stirring at 700 rpm at room temperature, yielding approximately 5 mg of Fe3O4 powder. Structural characterization via X-ray diffraction (XRD) confirmed the stoichiometric composition and particle dimensions. To enhance functionality, the Fe3O4 NPs were coated with chitosan (Cs), polyethylene glycol (PEG), and folic acid (FA), and loaded with the anticancer drug paclitaxel (PTX), forming nanoencapsulated Fe3O4@Cs-PEG-PTX-FA particles with sizes ranging from 100 to 130 nm. Magnetic properties were assessed using a vibrating sample magnetometer (VSM), revealing saturation magnetization (Ms) values of 59.6 emu/mg for Fe3O4 and 19.9 emu/mg for Fe3O4@Cs-PEG-PTX-FA. Encapsulation efficiency of 82.4% and drug-loading content of 14.4% were achieved. These results demonstrate the potential of Fe3O4 NPs as multifunctional agents in the biomedical field, particularly for targeted drug delivery systems, where magnetic properties can facilitate precise localization and release of therapeutic agents. In addition to size uniformity, biocompatibility, and responsiveness to external magnetic fields make, these properties make them promising candidates for cancer treatment, particularly in targeting fibrosarcoma cells.